Difficulties regarding the development of teaching skills that Student teachers of the English teaching major face when carrying out their teaching practice in the different subjects of the Foreign Language Department at the University of El Salvador in the year 2017 - Osorio Ramón, Yoselin Iveth; Rivera Espino, Erika María; Sánchez Mejía, Evelyn Madari (2024)
The main purpose of this research was to acknowledge the difficulties that StudentsTeachers that were assigned to the Foreign Language Department in the different subjects faced when carrying out their teaching practice. From the lack of experience, the deficit in orientation and the necessity to improve their language competence and other difficulties, this research addressed those issues that concerned and affected the performance of the participants. The motivation acquired by the researchers to investigate about this topic was the importance that this phase has on the student’s instruction and their future professional life and the well-known fact that teaching is a long lasting process in which an individual never stops acquiring knowledge and learning new strategies to convey an outstanding role in someone else´s educational process. The researchers wanted to explore this topic because there is a need for StudentTeachers to discover effective ways to foster their confidence, work on their teaching skills, practice adequate teaching classroom strategies and achieve good quality background in higher education or other level that he or she gets assigned to work in the future. According to Tom Drummond in his work “A brief summary of the best practices in college teaching, 2008” great teachers teach by example. It is the authentic life that instructs and there are challenges in every action he or she takes to engage, facilitate and give life to the opportunity to learn